Endovascular closure of patent foramen ovale for cryptogenic stroke prevention in patients of young age - Ditkivskyy, I. O.; Mazur, O. A.; Yashchuk, N. S.; Cherpak, B. V.; Yermolovych, Ju. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
One of the causes of cryptogenic stroke in young and middle-aged patients is patent foramen ovale (PFO), which enables paradoxical embolism of cerebral arteries by thrombi from systemic veins. According to latest research, endovascular PFO closure is the optimal method for the prevention of further cryptogenic stroke. From 2011 to 2018 y 10 procedures of endovascular PFO closure with an occluder in young patients with cryptogenic stroke and paradoxical systemic embolism were performed in National M. M. Amosov Institute of Cardiovascular Surgery. The success rate was 100%, and there were no serious complications in the postoperative and long-term periods. All patients are alive and are reporting subjective improvement (headaches and migraines were gone). In one case 1.5 years after the procedure there was reported an MRI-confirmed ischemic stroke, without residual effects. Its most probable reason was embolism with microthrombi from left atrial appendage (there was reported arrhythmia of undetermined etiology in this patient), because both Doppler echocardiography and bubble-test showed no shunt between right and left heart. Our data confirms the effectiveness and safety of endovascular PFO closure for the prevention of cryptogenic thromboembolism.